Plasma metabolomic profiling of healthy pregnant mares and mares with experimentally induced placentitis. (15th April 2020) - Beachler, Theresa M.; Gracz, Hanna S.; Morgan, David R.; Bembenek Bailey, Stasia A.; Borst, Luke; Ellis, Katey E.; Von Dollen, Karen A.; Lyle, Sara K.; Nebel, Amber; Andrews, Natalie C.; Koipalli, Joanna; Gadsby, John E.; et al.
Abstract: Background: Metabolomics may represent an avenue for diagnosis of equine ascending placentitis. Objectives: To characterise the plasma metabolomic profile in healthy mares and mares with induced ascending placentitis, with the goal of identifying metabolites with potential clinical value for early diagnosis of placentitis. Study design: Controlled in vivo experiment. Methods: Placentitis was induced in 10 late‐term pregnant pony mares via Streptococcal equi subsp. zooepidemicus inoculation in five mares between days 285 and 290 of gestation, while five mares served as healthy controls. Repeated ultrasound examinations and jugular venipuncture were performed to obtain combined thickness of the uterus and placenta (CTUP) and plasma for NMR spectroscopy. Mares with increased CTUP were diagnosed with placentitis and treated in accordance with published therapeutic recommendations. NMR metabolomic analysis was performed to identify and quantify plasma metabolites at each time point. Concentrations were compared using ANOVA with repeated‐measures and PLS‐DA analysis. Results: Four hours post‐inoculation, a significant increase was detected in the metabolites alanine, phenylalanine, histidine, pyruvate, citrate, glucose, creatine, glycolate, lactate and 3‐hydroxyisobutyrate that returned to baseline by 12 hours. On day 4, a significant reduction in the metabolites alanine, phenylalanine, histidine, tyrosine, pyruvate, citrate, glycolate, lactate and dimethylsulfone was seen in infected mares compared with controls. Main limitations: There were small numbers of mares within groups. In addition, this work compares healthy animals with animals treated with multimodal therapeutics following diagnosis of placentitis without an untreated cohort. Conclusions: Two phases of metabolite changes were noted after experimental infection: An immediate rise in metabolite concentration involved in energy, nitrogen, hydrogen and oxygen metabolism within 4 hours after inoculation that was followed by a decrease in metabolite concentrations involved in energy and nitrogen metabolism at 4 days, coinciding with ultrasonographic diagnosis of placentitis.